Vella - Gerchikov, Vladimir (Russia : Studio Telemost, 2005)
This documentary follows Yuri Vella, writer and social activist of the Forest Nenets living in West-Siberia. He left his home village ten years ago to lead the life of a reindeer herder in the taiga. The little unique world he created there was meant to offer protection from the alcoholism and unemployment that sadly poses a serious threat to the indigenous peoples of Siberia. To give his grandchildren proper education in their natural environment and teach them reindeer herding skills, he establishes an elementary school in his winter camp. Unfortunately, Yuri Vella's world is but an oasis of traditional lifestyle in one of the largest oil-producing regions of Russia. When he stands up against Lukoil Company, he ends up being caught in one civil action and two criminal cases.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films